Endoscopic characteristics to differentiate SSLs and microvesicular hyperplastic polyps from goblet cell-rich hyperplastic polyps - Toyoshima, Osamu; Nishizawa, Toshihiro; Watanabe, Hidenobu; Matsuno, Tatsuya; Yoshida, Shuntaro; Takahashi, Yoshiyuki; Mizutani, Hiroya; Ebinuma, Hirotoshi; Fujishiro, Mitsuhiro; Saito, Yutaka (Endoscopy International Open, 2024)
Background and study aims Among colorectal serrated polyps (SPs), sessile serrated lesions (SSLs) and hyperplastic polyps (HPs) have a similar endoscopic appearance. However, the endoscopic distinctions between those two categories, microvesicular HPs (MVHPs) and goblet cell-rich HPs (GCHPs), are not well understood. Therefore, we compared the endoscopic features of SSLs, MVHPs, and GCHPs.Methods This retrospective, cross-sectional study was conducted at the Toyoshima Endoscopy Clinic. We examined polyp size, location, Paris classification type, mucus cap, indistinct border, expanded crypt opening, varicose microvascular vessels, and JNET classification type. Multivariable analysis of each endoscopic finding using a binomial logistic regression model determined the factors that predicted SP histology.Results A total of 670 SPs were enrolled in this study, comprising 159 SSLs, 361 MVHPs, and 150 GCHPs. On comparing the SSL + MVHP group and the GCHP group, a mucus cap (partial regression coefficient 1.705), expanded crypt opening (1.828), and varicose microvascular vessels (1.270) were more often observed in the SSL + MVHP group compared with the GCHP group. In the comparison between MVHPs and GCHPs, a mucus cap (1.564), expanded crypt opening (1.802), and varicose microvascular vessels (1.288) were more often found in MVHPs in contrast to GCHPs. When comparing SSLs and MVHPs, SSLs were more likely to be in the proximal colon (0.662) and were larger (0.198) than the MVHPs. No significant differences were observed in other endoscopic findings.Conclusions SSLs and MVHPs have endoscopic appearances that differ from those of GCHPs. Considering MVHPs and GCHPs as distinct entities may aid in endoscopic diagnosis of SPs.
Keywords: Endoscopy Lower GI Tract; Polyps / adenomas / ...; Tissue diagnosis; GI Pathology